2015
DOI: 10.1021/acs.jafc.5b04453
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Glyphosate and Aminomethylphosphonic Acid in Nutritional Ingredients and Milk by Derivatization with Fluorenylmethyloxycarbonyl Chloride and Liquid Chromatography–Mass Spectrometry

Abstract: A straightforward analytical method based on derivatization with fluorenylmethyloxycarbonyl chloride and liquid chromatography-mass spectrometry has been developed for the analysis of residues of glyphosate and aminomethylphosphonic acid (AMPA) in a suite of nutritional ingredients derived from soybean, corn, and sugar beet and also in cow's milk and human breast milk. Accuracy and intermediate precision were 91-116% and <10% RSD, respectively, in soy protein isolate. Limits of quantitation were 0.05 and 0.005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
(67 reference statements)
0
42
0
Order By: Relevance
“…Stock solutions containing either one or the two analytes at 200 mg/L in 0.1 M HCl were prepared. Acidification with HCl to pH 1 has been found to be necessary in the case of environmental samples since multivalent cations form stable complexes with GLP and AMPA, which are not derivatized [11,20,[25][26][27]32,33]. All standard and working solutions were stored at 4 • C in polypropylene material given that GLP binds to active sites on glass when it is not derivatized [22,24,27].…”
Section: Reagents and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stock solutions containing either one or the two analytes at 200 mg/L in 0.1 M HCl were prepared. Acidification with HCl to pH 1 has been found to be necessary in the case of environmental samples since multivalent cations form stable complexes with GLP and AMPA, which are not derivatized [11,20,[25][26][27]32,33]. All standard and working solutions were stored at 4 • C in polypropylene material given that GLP binds to active sites on glass when it is not derivatized [22,24,27].…”
Section: Reagents and Solutionsmentioning
confidence: 99%
“…However, other studies found optimum reaction times of 30 min [18,22,23] and 60 min [24]. Once the prefixed derivatization time is achieved, the solution must be acidified to stop the reaction and to obtain stable derivatives for some days [20][21][22][25][26][27]. Due to the stability of FMOC derivatives, this reagent is applied as a precolumn derivatization reaction.…”
mentioning
confidence: 99%
“…Two papers published in 2015 reported the GLYP, AMPA, and GLUF determination in milk and milk-based products. Ehling and Reddy carried out a derivatization with FMOC-Cl followed by means of LC-MS/MS in different nutritional milk matrices such as cow's milk, human breast milk, soy milk, and whole milk powder [98]. This study is important because the reported analytical method does not require any analytical treatment such as clean-up, evaporation, or concentration; so, the possible artifact formation is drastically reduced.…”
Section: Beveragesmentioning
confidence: 99%
“…Overall, these methods are relatively complicated and time-consuming. Furthermore, the use of derivatization agent typically requires the nonvolatile buffer of borates to adjust the pH values, and the borates can result in signal instability and formation of salt deposits [19,20,31,32]. Besides avoiding the derivatizaiton step, this method also needs no preconcentration step for obtaining high sensitivity.…”
Section: Comparison To Previous Reportsmentioning
confidence: 99%